System analysis of interaction of decision-making tasks - Чаплінський, Ю. П. (Problems of Informatization and Control, 2007)
The systematized description of interaction of decision-making tasks is presented. The decision-making situations of interrelation of different decision-making areas are analyzed. The decision-making process is described for tasks which are formulated in the class of tasks of the mathematical programming